1996
DOI: 10.1136/adc.75.5.427
|View full text |Cite
|
Sign up to set email alerts
|

Model of normal prepubertal growth.

Abstract: Growth over the short term is a highly complex non-linear process. Contrasting models of short term growth have been proposed which include periodic growth cycles versus abrupt growth spurts with intervening growth arrest ('saltation and stasis'). The variability of short term growth has been characterised from a study of 46 healthy prepubertal children measured three times a week over one academic year using a combination of descriptive statistical approaches and regression modelling. Growth in childhood over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
0
1

Year Published

1998
1998
2019
2019

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(40 citation statements)
references
References 19 publications
2
37
0
1
Order By: Relevance
“…The authors concluded that their data were incompatible with the saltatory model. Similar findings were published by us [74], and further longitudinal studies have shown that only a minority of gain in stature can be said to be truly saltatory [75]. It was suggested that alternate series of saltatory events and stasis simply are a result of the assumptions of the mathematical model as the model only allows ‘increase’ (saltation), or ‘no increase’ (stasis).…”
Section: The Physiology Of Short-term Growthsupporting
confidence: 68%
“…The authors concluded that their data were incompatible with the saltatory model. Similar findings were published by us [74], and further longitudinal studies have shown that only a minority of gain in stature can be said to be truly saltatory [75]. It was suggested that alternate series of saltatory events and stasis simply are a result of the assumptions of the mathematical model as the model only allows ‘increase’ (saltation), or ‘no increase’ (stasis).…”
Section: The Physiology Of Short-term Growthsupporting
confidence: 68%
“…Successive measurements of growth velocity are not well correlated because of the cyclical nature of growth over the short (1-yr) and longer term (2-yrs) [25,26]. Given the cyclical nature of growth, control data are essential for any study and, because of the longer-term trends in childhood growth ( fig.…”
Section: Growth During Childhoodmentioning
confidence: 99%
“…Infants and young children in particular are expected to demonstrate progressive weight gain and linear growth, a process that does not proceed in a predictable linear manner. 192 Thus, it is unreasonable to expect that pediatric patients can achieve and maintain a stable dry weight. Two potential approaches to this problem have been studied: bioimpedance analysis and blood volume monitoring.…”
Section: Hypertension In Pediatric Dialysis Patientsmentioning
confidence: 99%